Oral Health of Lipjan Convicts: Kosovo Prison House - Luljeta Zajmi; Agim Begzati; Milaim Sejdini; Nora Berisha; Lumnije Krasniqi (International Journal of Dentistry)
Objectives. The oral health services of the prison population are considered more complex than those of the general population. The aim of this study was to examine the oral health status (the DMFT index and OHI index) and to evaluate the relation between the oral health and risk factors of inmates of this population, thus identifying the dental health status of inmates by gender, age, and the duration of their sentence. Materials and Methods. Our study has included a total number of 150 inmates, of both genders, from Lipjan prison house in Kosovo. Results. Oral health condition of inmates in Lipjan prison house is severe; the average value of DMFT is 8.44: for minors 6.22, while for adults 9.55. The assessment of DMFT index within the recruited inmates in our study shows that the mean rate of oral cure was 3.21, while the mean extraction value and caries were 3.55 and 3.58, respectively. The mean plaque test value was 1.44. Conclusion. Based on this research, we have concluded that the oral health condition of the inmates in Lipjan prison is not good, due to the presence of different risk factors among them.